PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TS-TS) PADA SISWA KELAS VII.4 - Yahya Yahya (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a classroom action research, by improving mathematics learning outcomes through cooperative learning model type Two Stay Two Stray (TS-TS). The results of the study indicate that the use of the l Two Stay Two Stray (TS-TS) learning model can increase the activeness and learning outcomes of class VII-4 students in mathematics at SMP Negeri 26 Makassar. This can be seen from the increase in student learning activity, the percentage in the first cycle of 49.2% increased in the second cycle to 61.6% and increased again in the third cycle to 70.7%. In addition, this learning model can improve student learning outcomes. In the first cycle of action tests students who completed 45%, the second cycle increased to 83%, and increased to 100% in the third cycle. So it can be concluded if the application of the model can increase student activity and learning outcomes.